Influence of metalworking defect in knee cruciate ligament screws as a possible origin of infections - Spector, Mario (2015)
A mucormycosis outbreak in a a clinic of Paraná city after Arthroscopic knee anterior cruciate ligament reconstruction forced to suspend these interventions. The the main candidates as the infection source were the implanted screws. These screws were metallurgically analyzed. Microscopic defects like burrs and bending`s were found within the screw´s allen heads. According to Spector et al. (2013) these defects protect microorganisms and make difficult to eliminate them. The aim of this work was to demonstrate the implication of metal working defects in the titanium fixing screws as a reservoir of contaminated machining oil which could be the possible transmitting vehicle in the outbreak of bone mucormycosis. The genetic relatedness of the isolated strains was established demonstrating that the screws were the infection sources.